Epidemiosurveillance of Brucella infection in humans, non-ruminants and wildlife from Pakistan perspective (2000-2020) - ZEESHAN AKRAM, M; ULLAH KHAN, A; SHAUKAT ALI, B; SHAHID, S; BATOOL, A (Journal of the Hellenic Veterinary Medical Society, 2021)
This review aimed at providing an overview of the prevalence and epidemiosurveillance of brucellosis in non-ruminants and humans in Pakistan during 2000-2020. Sero-prevalence of brucellosis has been reported in non-ruminants such as camels, equines, dogs and humans with the range of 0.5-21%, 16.23-62.6%, 9.2-63.8% and 2.0-70% respectively. Non-target species like Avian, reptiles and amphibians were also reported with the prevalence of 2.5%, 24.9% and 25% respectively. Ignorance and indifference make it endemic in ruminants and much-neglected disease in non-ruminants with less or no studies reported in canines. Vaccines are available and being used for ruminants while none is available for non-ruminants, which may serve as an important source of spreading disease in animals and humans. In Pakistan, it is considered as ignored disease in non-ruminants lacking effective policies for control and eradication. This review guides policymakers to draw guidelines regarding brucellosis control and eradication using one health approach.